UGT2B17 Genotype and the Pharmacokinetic Serum Profile of Testosterone during Substitution Therapy with Testosterone Undecanoate. A Retrospective Experience from 207 Men with Hypogonadism - Bang, Anne Kirstine; Jørgensen, Niels; Rajpert-De Meyts, Ewa; Juul, Anders (Frontiers in Endocrinology, 2013)
Background Testosterone (T) is mainly excreted in the urine as testosterone glucuronide (TG). This glucuronidation is partly dependent on the UGT2B17 genotype, and TG excretion is therefore lower in men having the UGT2B17 deletion. However, the possible influence of UGT2B17 genotype on serum T during androgen therapy is unknown. We retrospectively investigated the possible association between the UGT2B17 gene polymorphism and serum T levels in hypogonadal men during Testosterone undecanoate (TU) substitution therapy. Subjects and methods 207 patients treated with TU (Nebido®) were genotyped by qPCR for the UGT2B17 deletion polymorphism. All were given 1000 mg TU per injection at 0, 6 and 18 weeks. Blood samples were taken 2 and 6 weeks after the 1st and 2nd injection, prior to the 3rd injection, and after 2-3 years of treatment. We analysed for the levels of T, luteinizing hormone, sex-hormone-binding globulin, estradiol, prostate specific antigen, haematocrit, haemoglobin and total cholesterol. Results The UGT2B17 genotype frequency was: ins/ins: 42%, ins/del: 44% and del/del: 14%. During the initial 18 weeks of TU treatment, large intra- and inter-individual variations in serum T levels were observed. Large peaks in T levels, ranging from 6.7 nmol/l to 69.5 nmol/l, were noted 2 weeks after injections, regardless of the genotype. T levels did not differ between the 3 genotypes prior to the 3rd injection, but the del/del group had significantly lower levels of LH. At follow-up after 2-3 years, the injection interval or daily T dosage was not dependent on the UGT2B17 genotype. Conclusion In conclusion, we found large intra- and inter-individual variations in serum T during standard TU treatment regimen in hypogonadal men. Only subtle differences in serum T and LH were noted according to UGT2B17 genotype, which however suggest that the UGT2B17 genotype exert modest influence on the pharmacokinetic profile of T after TU treatment.